Analysis on different shape of textile antenna under bending condition for GPS application - N. I. Zaidi; M. T. Ali; N. H. Abd Rahman; M. F. Yahya; M. S. Amin Nordin (Bulletin of Electrical Engineering and Informatics, 2020)
In this paper, three antennas with different designs, which are square, circle and edgy patch (flower) were simulated and fabricated. The experiment was carried out to study the effects of bending on these three different shapes of antennas. Two bending conditions which are H-plane and E-plane were used. The antenna was designed to resonate at 1.575 GHz for GPS application and to be incorporated with human arm. Thus, the bending angle was specified to be 135o which is about the size of a typical human arm. As the paper focusing on the bending effects only, the characteristic of the bending structure was set to be equal to the air, with Ɛr=1. The antenna characteristics such as gain, resonant frequency and radiation pattern were analyzed for these three shapes of antennas. As a result, the shape of the radiating patch has significant impact on the antenna performance under bending conditions. Based on the comparison of E-plane and H-plane data, the edgy shape was found to be more affected in term of gain performance as compared to other shapes. Bending on E-plane has shown severe degradation in antenna gain performance, whereby at H-plane, significant improvement in gain was observed